Sequence of the distal tRNA1Asp gene and the transcription termination signal in the Escherichia coli ribosomal RNA operon rrnF(or G). - Sekiya, T (1980)
Several DNA fragments carrying tRNA genes have been cloned from EcoRI endonuclease digests of Escherichia coli DNA. Using cloned DNA, the sequence of the region around the distal gene for tRNA1Asp (F(or G)) in the E. coli ribosomal RNA operon [rrnF(or G)] has been determined. In the distal portion of rrnF(or G), the genes for 23S, 5S rRNA and tRNA1Asp (F(or G)) are located in that order and separated by intergenic spacers of 93 and 52 base pairs, respectively. A possible hairpin structure, with its center between the 22nd and 23rd base pair downstream from the 3'-end of the tRNA1Asp(F(or G)) gene, followed by a sequence of eight thymidine residues was identified as the transcription termination signal for rrnF(or G). The termination is rho-independent, at least in vitro, and occurs within the region of the contiguous thymidine residues. A possible promoter for a protein gene is present about 50 base pairs downstream from the rrnF(or G) terminator.